Regulation of nitrogen-fixing symbioses in legumes - Frendo, Pierre; Masson-Boivin, Catherine; Frugier, Florian (Advances in botanical research, 2020)
The Nitrogen-Fixing Legume-Rhizobium Symbiosis, Volume 94, the latest release in the Advances in Botanical Research series, highlights new advances in the field, with this new volume presenting interesting chapters on The diversity of legume-rhizobium symbioses, Parasponia; an evolutionary outlier of rhizobium symbiosis, Rhizobium diversity in the light of evolution, Genomes of rhizobia, Gene regulation by extracytoplasmic function (ECF) sigma factors in alpha-rhizobia, Early symbiotic signaling between Plant and Bacteria, Rhizobia infection, a journey to the inside of plant cells, Differentiation of symbiotic nodule cells and their rhizobium endosymbionts, Nodule Organogenesis, Nitrogen Fixation by the Legume-Rhizobium Symbiosis, and much more. --